Adjusting the nutrient solution formula based on growth stages to promote the yield and quality of strawberry in greenhouse - Yu, Weizhong; Zheng, Jianfeng; Wang, Yingli; Ji, Fang; Zhu, Baoying (International Journal of Agricultural and Biological Engineering, 2023)
To optimize the nutrient supply of strawberry, fertilization was reduced as much as possible on the premise of satisfying the elements needed for strawberry growth. This study put forward a modified nutrient solution formula (NM) by adjusting the ratios of N/K, K/Ca, NO3–N/NH4+-N in vegetative growth, flowering and fruiting, and fruit expanding stages based on Yamasaki strawberry nutrient solution formula (NY). Taking the NY as the control group, the NM was verified with elevated-grown ’Ssanta’ strawberry using three different substrates (Vulcanics-added substrate, Horticultural substrate, Commercial substrate) in greenhouse. The results indicated that under the NM treatment, strawberry plants had better photosynthesis in the vegetative growth stage and flowering and fruiting stage, and the first crop yield and total crops yield per plant also increased by 20%. Although the vegetative growth stage was longer, it entered the full fruiting stage earlier so that the maturity stage was advanced one week. Compared to strawberries grown in horticultural substrate irrigated with NY, the fruit yield per plant of ‘Ssanta’ strawberry grown in horticultural substrate irrigated with NM increased by 26%, and the sugar-acid ratio and vitamin C content of primary fruits reached 10.6 and 74.1 mg/100g, improving by 41% and 34% respectively. The NM based on the growth stage can optimize the element needs of strawberry in all growth and development stages and maintain the substrate’s pH stability, improving the yield and quality of ’Ssanta’ strawberry under substrate cultivation. Therefore, it is recommended to use the horticultural substrate irrigated with the modified nutrient solution for the ’Ssanta’ strawberries cultivation elevated in greenhouse to improve the economic benefit of strawberry cultivation. Keywords: elevated-grown strawberry, nutrient solution formula, substrate cultivation, phenological stage, fruit yield, fruit quality DOI: 10.25165/j.ijabe.20231602.7797 Citation: Yu W Z, Zheng J F, Wang Y L, Ji F, Zhu B Y. Adjusting the nutrient solution formula based on growth stages to promote the yield and quality of strawberry in greenhouse. Int J Agric & Biol Eng, 2023; 16(2): 57-64.